Is the persistence of Listeria monocytogenes in food processing facilities and its resistance to pathogen intervention linked to its phylogeny? - van de Merwe, Chandré; Simpson, David J.; Qiao, Nanzhen; Otto, Simon J. G.; Kovacevic, Jovana; Gänzle, Michael G.; McMullen, Lynn M. (Applied and environmental microbiology, 2024)
Listeria monocytogenes substantially contributes to the mortality of foodborne disease in developed countries. The virulence of strains of four lineages of L. monocytogenes differs, indicating that risks associated with the presence of L. monocytogenes are lineage specific. Our study extends the current knowledge by documentation that the lineage-level phylogeny of L. monocytogenes plays a role in the source of isolation, in the persistence in food processing facilities, and in the resistance to pathogen intervention technologies. In short, the control of risks associated with the presence of L. monocytogenes in food is also lineage specific. Understanding the route of contamination L. monocytogenes is an important factor to consider when designing improved control measures.